Over-Expression of LcPDS, LcZDS, and LcCRTISO, Genes From Wolfberry for Carotenoid Biosynthesis, Enhanced Carotenoid Accumulation, and Salt Tolerance in Tobacco - Li, Chen; Ji, Jing; Wang, Gang; Li, Zhaodi; Wang, Yurong; Fan, Yajun (Frontiers in Plant Science, 2020)
It is of great importance to combine stress tolerance and plant quality for breeding research. In this study, the correlation and comparison among phytoene desaturase (PDS), ζ-carotene desaturase (ZDS) and carotenoid isomerase (CRTISO) on carotenoids biosynthesis are reported. The three genes were derived from Lycium chinenses, which were involved in the desaturation of tetraterpene, and their over-expressions enhanced carotenoids accumulation, photosynthesis and salt tolerance in tobacco respectively. Under salt stress, proline content and activities of antioxidative enzymes increased more, meanwhile reactive oxygen species accumulated less in the three over-expressors. The balance of carotenoids biosynthesis was rebuilt via regulating the expression of related genes, thus enhanced carotenoids accumulation and salt tolerance in the over-expressors. Meanwhile, lycopene was found as a key constituent to deal with oxidative damages caused by salt stress, which is the direct production of the desaturation of tetraterpene. This study offered new viewpoints on regulating procedures in carotenoids biosynthesis, and showed the potential of these genes for improving carotenoids content and enhancing salt tolerance in higher plants for further researches.